2016
DOI: 10.1177/1076029616642511
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Use in Patients With Nonvalvular Atrial Fibrillation: Has Prescribing Improved?

Abstract: Discordance between international guideline recommendations and anticoagulant prescribing patterns among patients with nonvalvular atrial fibrillation (NVAF) has been frequently reported. This study was designed to compare the anticoagulant utilization pattern to earlier data in the same population and identify predictors of anticoagulant prescribing among patients with NVAF. We reviewed patients with NVAF admitted to Tasmania's 3 major hospitals between January 2011 and June 2012 and compared the anticoagulan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
6
0
2
Order By: Relevance
“…Despite controversy regarding its efficacy and safety, some guidelines continue to suggest low‐dose aspirin in patients with low to moderate risk of stroke (CHA 2 DS 2 ‐VASc score=0‐1) as an alternative to OAC therapy . Observational studies have typically demonstrated under‐use of anticoagulants in patients who are eligible to receive them and that antiplatelet agents are commonly used among patients with AF including those at higher risk of stroke (CHADS 2 or CHA 2 DS 2 ‐VASc≥2) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite controversy regarding its efficacy and safety, some guidelines continue to suggest low‐dose aspirin in patients with low to moderate risk of stroke (CHA 2 DS 2 ‐VASc score=0‐1) as an alternative to OAC therapy . Observational studies have typically demonstrated under‐use of anticoagulants in patients who are eligible to receive them and that antiplatelet agents are commonly used among patients with AF including those at higher risk of stroke (CHADS 2 or CHA 2 DS 2 ‐VASc≥2) …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Observational studies have typically demonstrated underuse of anticoagulants in patients who are eligible to receive them and that antiplatelet agents are commonly used among patients with AF including those at higher risk of stroke (CHADS 2 or CHA 2 DS 2 -VASc≥2). [10][11][12][13] Since the 1950s, vitamin K antagonists (VKAs) were the only available OACs and most widely used antithrombotic agents for stroke prophylaxis in patients with AF. 14,15 In recent years, four direct oral anticoagulants (DOACs), namely dabigatran, rivaroxaban, apixaban, and edoxaban, have been approved for the prevention of stroke associated with nonvalvular AF (NVAF).…”
mentioning
confidence: 99%
“…Interestingly, after the introduction of the DOACs, similar rates of anticoagulant prescribing to high-risk patients have been reported by Pandya et al [28] of 54% from a hospital in New South Wales. Three Tasmanian studies have also reported comparable rates with studies by Bista et al in the early post-DOAC era finding 52.5% [29] and 55.6% [30] of high-risk patients received anticoagulants, while Admassie et al [20] found this increased to 60.7% in a study ranging from 2010 to 2015. Further to this, in rural Western Australia Bellinge et al [31] found 69% of patients with AF received oral anticoagulant therapy during hospital admission, but this was for patients with a CHA₂DS₂VASc scores ≥ 1.…”
Section: Resultsmentioning
confidence: 52%
“…A recent analysis of OAC prescribing in AF in the same population showed the proportion of patients with AF receiving OACs increased significantly over the study period. 11,19 Second, DOACs are increasingly used in patients with nonvalvular AF in preference to warfarin. 4,10 Comparative analysis involving warfarin-treated patients in this study also indicated no significant difference in the overall TE, IS/TIA, and all-cause mortality incidence rates between the 2 eras (data not shown).…”
Section: Discussionmentioning
confidence: 99%